2013
DOI: 10.1097/01.jaa.0000430342.95024.13
|View full text |Cite
|
Sign up to set email alerts
|

Career patterns of physician assistants

Abstract: Most PAs change specialties during their career, and this trait of the profession is highly valued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Those in the career regret group reported less control over their schedule than those without regret. This supports prior research showing that lack of control over one’s schedule is one of the largest predictors of career regret ( Warner, Maio and Hudmon, 2013 ; Peckham, 2015 ). Employers can help prevent burnout and career regret by accommodating individual schedules and needs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Those in the career regret group reported less control over their schedule than those without regret. This supports prior research showing that lack of control over one’s schedule is one of the largest predictors of career regret ( Warner, Maio and Hudmon, 2013 ; Peckham, 2015 ). Employers can help prevent burnout and career regret by accommodating individual schedules and needs.…”
Section: Discussionsupporting
confidence: 88%
“…Control over one’s practice environment was cited as the most important contributor to practice satisfaction in both physicians ( Peckham, 2015 ) and PAs ( Warner, Maio and Hudmon, 2013 ). Elements that contribute to career regret among physicians include declining incomes, excessive paperwork, electronic health records and working too many hours ( Adams, 2012 ; Peckham, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This model maintains proactive flexibility, an attractive and distinguishing feature of the PA profession. [13][14][15] However, the absence of formal postprofessional training in this model may limit opportunities for PAs to achieve parity within or outside clinical practice and may limit opportunities for leadership and scholarship.…”
Section: Physical Therapymentioning
confidence: 99%
“…Switching specialties is common over the course of a PA career. A study of PAs who graduated between 1978 and 1998 found that 75% changed specialties at least once during their career 2. This same study noted that PAs worked in an average of 1.95 specialty practices per decade 2.…”
mentioning
confidence: 97%
“…A study of PAs who graduated between 1978 and 1998 found that 75% changed specialties at least once during their career 2. This same study noted that PAs worked in an average of 1.95 specialty practices per decade 2. Another study found that over 4 decades, 49% of active PAs had practiced in at least two specialties, and 10% reported at least three specialties 3…”
mentioning
confidence: 99%